Smoking addiction and its toxic influence on the oral health - Pluta, Małgorzata; Nasiłowska-Barud, Alicja (Polish Journal of Public Health, 2012)
Introduction. Harmful effect of cigarettes, in particular, the toxic influence of tarry substances in the tobacco smoke has been described in various publications and scientific works. Numerous symptoms of this adverse influence can be observed within the oral cavity, among others, in saliva composition, the state of enamel surface and the change in the mineral structure of teeth as well as changes in the mucous membrane and within the tongue. Aim. The aim of the study is presentation of harmful influence of the tobacco smoke on the oral health state and dental prophylaxis as a means partially reducing the negative effects. Material and methods. Questionnaires defining the type of addiction and patients’ subjective extra-oral examination. The investigated were divided into three age groups and according to gender. Results. Decrease in smoking is observed in the youngest age group between 20 and 40 as well as in the group above the age of 60. In all smoking patients, dental plaque, calculus, discolorations are present and in half of the investigated periodontitis occur. All smokers experienced the problem of bad breath and only half of the investigated tried to resolve it. Proper hygiene habits were observed in 60% of the investigated. Conclusions. The study revealed positive effect of dental prophylaxis which decreases adverse influence of cigarettes on the oral health state.